Answer:
(f-4) = 24
Explanation:
f(x)=x^2-2x.
The given function is a function of x such that the value of the function at any time is determined by the value of x at that time. Therefore, the value of the function is determined by substituting a value for x in the equation, x^2-2x
We want to determine f(-4)
From the information given, x would take the value of -4
So x = -4. Therefore, we will substitute x = - 4 into equation x^2-2x
This becomes
f (-4) = (-4^2) - (2 × -4)
f(-4) = 16 + 8
(f-4) = 24
So the value of the function, f(x)=x^2-2x at (f-4) is 24